The First Pedagogic Experience of Vasily V. Kandinsky — the Letters from Munich to the Young Artist. Stating the Problem - Severtseva, Inga V. (Actual Problems of Theory and History of Art, 2014)
The Paris museum of rare letters and manuscripts (Musée des lettres et manuscrits) preserves the letters from Vasily V. Kandinsky, written during his living in Munich, to his friend A.A. Pappe. This correspondence from the early 1900’s gradually reveals the fundamental principles of the progressive European art education at the turn of the 20th century. Kandinsky was a student of the renowned art teacher Anton Azhbe, whose art studio was a center of the artistic learning and enlightenment for artists from Europe, the USA and Russia. Azhbe’s unique art system which nowadays became a part of the academic education was preserved due to the recollections of his contemporaries. The letters of Kandinsky to Pappe signifi cantly amplify the collection of the prominent writings devoted to this subject. However, the real value of these documents lies in the fact that this correspondence is the first documented evidence of the transfer of knowledge which would be the base of the pedagogical activities of the famous Russian avant-garde artist.
Keywords: V.V. Kandinsky; pedagogical approach of Vasily V. Kandinsky; Anton Azhbe; students of Anton Azhbe’s studio; European Art education at the turn of the 20th century